Islamic Education at Mughal Kingdom in India (1526-1857) - Suyanta, Sri; Ikhlas, Silfia (AT-TALIM, 2016)
One of the legacies of Islamic civilization in India was the Mughal dynasty that had encouraged the new revival of the old and almost drowned civilization. With the presence of this dynasty, the glory of India with Hindus civilization reappeared. Recorded in the history of Islam, the dynasty was established in the middle period. After the mid-over, there appeared three great kingdoms to rebuild the progress of Muslims. Among the major kingdoms were royal Mughal. The third crown can already be categorized as a superpower in those days, because the greatness of the kingdom had been able to organize the economic, political as well as military.. Islamic education at this time gained considerable attention. For this purpose, the royal Mughal made the mosque as a place of worship other than as a place of religious learning for the community. The mosque indeed had been provided with scholars who gave various lessons of religious knowledge. In fact, the mosques had also been completed with special rooms for students who wanted to stay for their education. Therefore, almost every mosque developed certain religious sciences with special teachers.